OC-054 The Value Of A Ward Liaison Nurse To Improve Endoscopy For In-patients. (9th June 2014) - Gaglia, A; Taggart, N; Williams, L; Flavell, L; Dahill, J; Haslam, N; Barkatali, R; Sarkar, S
Abstract : Introduction: Endoscopy Inpatients are challenging as they tend to be the sickest patients who require procedures urgently. The numbers fluctuate and there is little provision for capacity in a busy day-case endoscopy unit. At the Royal Liverpool there are >2000 in-patient endoscopic procedures per annum and which are served by 9 per week dedicated in-patient lists. However, these lists were poorly utilised at <50% of time this was due to cancellations and poor scheduling. Waiting times for in-patients were unacceptable. The aim was to improve the in-patient experience of endoscopy and improve efficiency of the in-patient lists. Methods: In February 2013, an In-patient liaison (B6) was appointed to help coordinate in-patient listing for endoscopy. This involved the triage of patients (including UGI Bleeds and ERCPs), coordinating with the wards and listing of patients. As the focal point of contact for ward teams, advice is given to teams about preparation of patients, as well as consenting patients on the wards ready for lists. Attending ward rounds on a daily basis to AandE, medical admissions unit and Gastroenterology wards means patients are actively listed. The effect was audited with outcomes of list utilisation, improvement patient waiting times and back-filling of lists. Results: Satisfaction Feedback from the ward staff, doctors and specialist nurses were extremely positive with the role. ERCPS were managed more effectively with reductions in cancellations of patients that did not require them and effective triage to EUS. Also access of patients needing urgent ERCP was much easier due to the value of coordination. UGI Bleeds Were managed more effectively which led to a reduction in the patients that required in-hours and out of hours theatre. Interventional Endoscopy Listing in-patients for complex therapeutic interventions such as stenting and getting tertiary referrals in form other hospitals was significantly improved. Efficiency The list utilisation improved greatly from 64 to 86% in just 8 months. The waiting times (patient scoped within 24 h of referral) improved by 32% for upper GI endoscopy and by 16% for sigmoidoscopy despite a substantial increase in the number of referral s (OGD increase by 13% and sigmoidoscopy by 20%). Conclusion: An in-patient liaison nurse has been pivotal for improving the quality, and efficiency, of the endoscopy service we offer to in-patients. Disclosure of Interest: None Declared.